Factors associated with knowledge about the health effects of exposure to secondhand smoke among youth in Bangladesh - Sultana, Rabeya (International Journal Of Community Medicine And Public Health, 2021)
Background: Despite the high prevalence of secondhand smoke exposure among Bangladeshi adults, little is known about the knowledge regarding the health effects of exposure to secondhand smoke among the youth aged 15-24 years in Bangladesh. Against this background, the present study was conducted among the youth in Bangladesh to ascertain their levels of knowledge regarding health effects of secondhand smoke and its associated factors. Methods: This was a cross-sectional study of 656 respondents between the age of 15-24 years old selected by multistage cluster sampling. This study was conducted in Dhaka Division, Bangladesh. Data was analyzed using Chi square testing and multivariate logistic regression. Results: The proportion of good, average and poor knowledge scores among respondents were 30.5%, 50.0% and 19.5% respectively. Age and education were significant independent predictors of good knowledge. Furthermore, education and gender were tended as independent predictor of average knowledge. OR for age: 1.12 (95% CI: 1.01 to 1.25); OR for education: 1.27 (95% CI: 1.15 to 1.40). Conclusions: Overall, the results of this study found that less than one-third of the youth had a good level of knowledge on secondhand smoke health effects. The government needs to focus more on less-educated individuals and adolescents if a successful policy is to be implemented.